STRESS KERJA DAN KOPING PADA GURU : A SYSTEMATIC LITERATURE REVIEW - Angga Wirayuda; Muhammad Nurwahidin; Sudjarwo Sudjarwo (Jurnal Ilmiah Hospitality, 2022)
Work stress is an individual's negative response to a job both physically and emotionally due to excess work ability limits. Coping stress is an individual's ability to handle the stress. Teachers are one of the jobs that can cause stress so teachers must have coping strategies to reduce it. This study aims to deepen teachers' job stress and coping factors in the epistemology of the philosophy of science using the method of systematic literature review (SLR). Literature sources are drawn from Google Scholar and Scopus databases for the last 10 years. From an academic perspective, the results of this study show that work stress and teachers' coping methods have an impact and correlation value that the use of coping methods can reduce work stress. The value of epistemology in this study is the causative factors of work stress and coping strategies to deal with it.